Feasibility of the "Hayuma" Ready-to-Wear Fashion Inspired by Kudus Kretek Dance and Weaving Technique - Lisdiana, Tri; Nurmasitah, Sita (Journal of Creativity Student, 2026)
Kudus Kretek Dance, as part of intangible cultural heritage, struggles to stay preserved because foreign culture dominates social media. Bringing local cultural heritage into modern fashion is a key way to revive culture, but past studies have used weaving techniques only as decorations, not as core construction. This research examines whether "Hayuma" ready-to-wear fashion can be inspired by Kudus Kretek Dance and incorporate weaving as a central element of its structure. A descriptive quantitative approach is used, backed by three fashion experts. The research tool is a validation sheet assessing six areas, including design, looks, size, sewing, garment performance, and product uniqueness, with a Guttman scale. Data were analyzed using a descriptive percentage method and understood using feasibility categories. "Hayuma" fashion scored 93.8% feasibility, placing it in the "Highly Feasible" category. The product blended elements of Kudus Kretek Dance with Kudus batik and tobacco-flower designs, and toh watu shawl and weaving on the sleeves, in a stylish, dramatic way for people aged 18-30. Conclusion: "Hayuma" ready-to-wear fashion is highly feasible for production and sale as a modern fashion item, boosting local cultural values, innovative weaving techniques, and quality crafts, helping to revitalize intangible cultural heritage through Indonesia's fashion industry.